2019
DOI: 10.1002/anie.201905087
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Behavior of a Hexamethylenetetramine‐Based Molecular Perovskite Structure

Abstract: We report the development of a molecular ferroelectric material inspired by the hexamethylenetetramine (hmta) non‐centrosymmetric molecular rotator. The bromide salt of diprotonated hmta (hmtaH2) crystalized as (hmtaH2)(NH4)Br3 in a metal‐free ABX3 perovskite‐type structure, in which the A and B sites are occupied by hmtaH22+ and ammonium cations, respectively. The compound crystallized in the Pma2 polar space group. A distorted polar perovskite structure formed owing to the distortion of {(NH4)Br6} octahedron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 20 publications
1
56
0
Order By: Relevance
“…Although not discussed in the respective papers, DOS calculations shown in refs. [4] and [9] for substituted DABCO materials can be interpreted as a support of this assignment of the lowest CB to the DABCO. The relatively flat bands seen in the calculated band diagram ( Figure 2C) reflect in real-space localization of orbitals and, in particular, localization of the VB.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Although not discussed in the respective papers, DOS calculations shown in refs. [4] and [9] for substituted DABCO materials can be interpreted as a support of this assignment of the lowest CB to the DABCO. The relatively flat bands seen in the calculated band diagram ( Figure 2C) reflect in real-space localization of orbitals and, in particular, localization of the VB.…”
supporting
confidence: 66%
“…[8] These materials are nontoxic, mechanically flexible, and lightweight compared to traditional metal-based halide perovskites. The functionality of these materials has recently been explored as metal-free ferroelectrics, [4,9] mechanical/elastic properties, [10][11][12] and their non-linear optical properties have been reported in a theoretical study. [13] Unfortunately, 17 years after the initial discovery of metal-free halide perovskites, there have been no reports about their charge transport characteristics and only one report (see Supporting Information of ref.…”
mentioning
confidence: 99%
“…+ was believed to be generated in situ by acid (HBr) hydrolysis of hmta: hmtaH + + 3H + + 6H 2 O → 4NH 4 + 6HCHO. [24] ANH 4 [BF 4 ] 3 perovskites were prepared using NH 4 BF 4 with H 3 PO 4 . [15,25]…”
Section: Crystal Synthesismentioning
confidence: 99%
“…It was followed the next year with a paper by Morita et al, who showed ferroelectric behavior in (hmta)NH 4 Br 3 . [24] hmta is also a component of solid fuel tablets and is also known as the active ingredient in pharmaceuticals (urethral disinfectants). hmtaNH 4 Br 3 exhibited ferroelectric behavior up to 400 K. The P-E loops measured using both single crystals ( Figure 3A) and polycrystalline pellets Figure 3B) showed ferroelectric behavior believed to originate from inversion of spontaneous polarization.…”
Section: Ferroelectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation